The Effect of Salary and Workload on The Performance of Employees at PT. Original Bird Nest Medan - Meidan Rika Buaya; HD. Melva Sitanggang; Adiwima Zebua (Universitas Muhammadiyah Malang, 2026)
This study investigates the effects of salary and workload on employee performance at PT. Original Bird Nest Medan. Using a quantitative, explanatory design, data were collected through structured questionnaires administered to all available employees using a saturated sampling technique (n = 50). The model examines salary (X1), workload (X2), and employee performance (Y) with indicators adapted from prior literature: salary (eligibility, work motivation, job satisfaction), workload (working conditions, use of working time, targets to be achieved), and performance (work quality, work quantity, task implementation, responsibility). Multiple linear regression was applied to estimate the partial and simultaneous effects of predictors on performance. The results show that salary has a positive and significant influence on employee performance (β = 0.242; t = 2.628; p = 0.012), and workload also has a positive and significant influence (β = 0.689; t = 7.490; p < 0.001). Simultaneously, salary and workload significantly predict employee performance (F = 48.686; p < 0.001). The model explains a substantial proportion of variance in performance, with Adjusted R² = 0.661 (≈66%) and R² = 0.674, indicating that the remaining 34% may be attributed to other organizational factors not included in this study. Theoretically, this study reinforces compensation and job-demand perspectives by demonstrating that performance outcomes are shaped by both financial rewards and the structuring of work demands. Practically, the findings suggest that organizations should align salary fairness and workload allocation with operational expectations to sustain optimal performance and reduce performance decline associated with perceived imbalance. Overall, the study underscores that integrated compensation and workload management is essential for strengthening employee performance in labor-intensive production contexts.